The effects of replacing fish meal or soy protein concentrate with wheat gluten on growth, whole-body composition, and the retention and apparent digestibility coefficient of amino acids in Japanese seabass (Lateolabrax japonicus) - Zhang, Yuexing; Wang, Linghua; Dong, Zhiyong; Changarawe, Samwel Mugeni; Huang, Liying; Hu, Jinwei; Storebakken, Trond; Shi, Bo (Frontiers in Physiology, 2023)
The aim of this study was to evaluate the effects of wheat gluten replacing fish meal (FM) or soy protein concentrate (SPC) on growth performance, feed utilization and nutrient digestibility and retention in Japanese seabass (Lateolabrax japonicus). Seven isonitrogenous (441 - 456 g kg-1 crude protein) and isocaloric (21.5 - 22.0 MJ kg-1 gross energy) diets were produced to replace 0, 33.3, 66.7 and 100% of FM or SPC with a mixture of wheat gluten, wheat and taurine (GWT, 77.5% wheat gluten, 20.5% wheat and 2.0% taurine), respectively. The results showed that gradual replacement of protein in FM with GWT had no significant effects on feed intake, whole-body composition, hepato- and viscerosomatic indexes, but resulted in a linear decrease of weight gain rate, feed efficiency, retentions of nitrogen, energy and essential amino acids (Arg, His, Ile, Leu, Lys, Met, Phe, Thr, Val), while the apparent digestibility of most essential amino acids (Cys, His, Leu, Lys, Phe) and total amino acid increased linearly. Replacement protein in SPC with GWT had no significant effects on feed intake, growth, feed conversion ratio, whole-body composition and hepatosomatic index, but resulted in linear decrease of nitrogen, energy and Met retentions, while digestibility of Cys and Met increased linearly. Overall, wheat gluten is a more effective alternative to replace protein in SPC than FM.